COMPARATIVE ANALYSIS OF THE USE OF DIFFERENT TYPES OF PERITONIZATION DURING CONSERVATIVE MYOMECTOMY AND ITS IMPACT ON THE REPRODUCTIVE FUNCTION OF WOMEN - Gasanov, Y.M. (World of Medicine and Biology, 2015)
The aim - studying of the remote results of conservative myomectomy. Materials and methods. Carried out a comprehensive survey and surveys of women after surgical treatment. Of the 119 patients in the study included 96 patients, 16 women lived in remote areas, and 7 changed their permanent place of residence. The results were evaluated using the criterion of Machimana for related samples. One of the criteria of efficiency of operative treatment is the nature of menstrual function after a myomectomy. First regular menstrual period after operation was often more abundant, which was probably due to trauma of the uterus, the development of tissue edema, aseptic inflammation, and decreased contractile activity of the myometrium. Results and discussion. The establishment of a regular menstrual cycle in 88 (91.7 percent) of the operated women occurred within the first 3 months. However, we find it difficult to evaluate the impact of myomectomy on this process, because physical therapy rehabilitation 86 (89,6%) patients had taken various hormonal preparations. Combined oral contraceptives used in 41 (42.7 per cent) were women. 45 (46.9 per cent) were prescribed a progestogen: 16 (16,7%) and 10 mg from 5 to 25 day menstrual cycle, the remaining 29 (30,2%) - only in the 2nd phase (from 16 to 25). The duration of admission ranged from 3 months to 1 year. The analysis of the nature of the menstrual cycle showed that after myomectomy significantly decreased the amount of lost during menstruation blood and duration of bleeding. Surviving after surgery heavy periods in 19 out of 21 patients were noted from the period of menarche. And only 2 (2,1%) patients 6-8 months after myomectomy noted a slight increase in blood loss during menstruation. After carrying out of conservative myomectomy decreased the number of all applicable complaints. Significantly fewer of the surveyed women began to disturb pains in the lower abdomen, heavy periods. Most often the pain syndrome in the postoperative period was associated with the presence of adhesions in the abdominal cavity and the presence of endometriosis of different localization, which was diagnosed during myomectomy. None of the patients during the observed period of time was not observed of urination disorders associated with the presence of fibroids. Further was prescribed progestin drugs for 3-12 months. Ovarian cysts were diagnostirovanna in 6 patients. Exacerbation of chronic inflammatory process of the pelvic organs during the observed period was recorded only in 9 (9,4%) of the operated women. And only the 1st treatment was carried out in the hospital and has demanded carrying out of operative laparoscopy. CONCLUSIONS. Thus, the analysis showed a positive effect of myomectomy on the normalization of the menstrual, childbearing functions of women with uterine myoma. The operation has allowed to get rid of pain syndrome and dysuric disorders a large number of patients.
Keywords: uterine fibroids; surgical treatment; peritonization; reproductive function